Intrapericardial Bronchogenic Cyst: An Unusual Clinical Entity. (15th December 2014) - Ugurlucan, Murat; Sayin, Omer Ali; Felten, Matthias; Oztas, Didem Melis; Cakir, Mehmet Semih; Barburoglu, Mehmet; Basaran, Murat; Alpagut, Ufuk; Dayioglu, Enver
Abstract : Mediastinal cysts are extremely rare clinical disorders. They usually have a pericardial origin. In this report, we present a 27-year-old male patient with a mediastinal bronchogenic cyst together with clinical presentation and management of the pathology.